Chick PTPsigma regulates the targeting of retinal axons within the optic tectum. - Rashid-Doubell, F; McKinnell, I; Aricescu, A; Sajnani, G; Stoker, A (2002)
Chick PTPsigma (cPTPsigma), also known as CRYPalpha, is a receptor-like protein tyrosine phosphatase found on axons and growth cones. Putative ligands for cPTPsigma are distributed within basement membranes and on glial end feet of the retina, optic nerve, and optic tectum, suggesting that cPTPsigma signaling is occurring along the whole retinotectal pathway. We have shown previously that cPTPsigma plays a role in supporting the retinal phase of axon outgrowth. Here we have now addressed the role of cPTPsigma within retinal axons as they undergo growth and topographic targeting in the optic tectum. With the use of retroviruses, a secretable cPTPsigma ectodomain was ectopically expressed in ovo in the developing chick optic tectum, with the aim of directly disrupting the function of endogenous cPTPsigma. In ovo, the secreted ectodomains accumulated at tectal sites in which cPTPsigma ligands are also specifically found, suggesting that they are binding to these endogenous ligands. Anterograde labeling of retinal axons entering these optic tecta revealed abnormal axonal phenotypes. These included the premature stalling and arborization of fibers, excessive pretectal arbor formation, and diffuse termination zones. Most of the defects were rostral of the predicted termination zone, indicating that cPTPsigma function is necessary for sustaining the growth of retinal axons over the optic tectum and for directing axons to their correct sites of termination. This demonstrates that regulation of cPTPsigma signaling in retinal axons is required for their topographic mapping, the first evidence of this function for a receptor-like protein tyrosine phosphatase in the retinotectal projection.